1989
DOI: 10.1177/002221948902200202
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Processing, Language Comprehension, and Reading Ability

Abstract: Previous research has indicated a relationship between reading ability and the integrity of certain phonological processing skills--skills that operate on the sound structure of language. This study shows how the deficient phonological processing skills of poor beginning readers can impair their comprehension of spoken phrases and sentences that are disambiguated by prosodic cues (i.e., pitch, stress, and pause). Following a brief summary of the available research literature, two new experiments are reported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…A fairly large body of evidence has supported the importance of phonological short-term memory to both spoken and written language in normal children (e.g., Mann et al, 1989) and in language-impaired children (Baddeley & Wilson, 1993;Gathercole et al, 1994). Baddeley and co-workers have demonstrated that impairments to short-term memory in children are associated with poor vocabulary and language skills (e.g., Baddeley & Wilson, 1993;Gathercole & Baddeley, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…A fairly large body of evidence has supported the importance of phonological short-term memory to both spoken and written language in normal children (e.g., Mann et al, 1989) and in language-impaired children (Baddeley & Wilson, 1993;Gathercole et al, 1994). Baddeley and co-workers have demonstrated that impairments to short-term memory in children are associated with poor vocabulary and language skills (e.g., Baddeley & Wilson, 1993;Gathercole & Baddeley, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Schreiber focused on the development of reading fluency in beginning readers, but he also speculated (Schreiber, 1987) that poor readers may have difficulty attaining reading fluency: poor readers, as with beginning readers, continue to use prosody as a primary cue for chunking speech and fail to recognize the need to make better use of other cues to phrasing in a text. Indeed, in a study of phonological processing and comprehension skills, Mann, Cowin, and Schoenheimer (1989) demonstrated that poor grade 4 readers' sensitivity to, and reliance on, prosodic cues resembled that of younger (i.e., grade 2), reading ability matched children. Further, a study conducted by Young and Bowers (in press) found that poor readers in grade 5 read significantly less fluently and expressively than their average-ability peers, even when accuracy and rate were equivalent between the groups.…”
mentioning
confidence: 99%
“…Nor must we forget to bear in mind that giving the client his freedom to express his ideas overtly, candidly, and also publicly directly after using DAF play an important role in his treatment of which sentence structure was the most difficult step. However, Mann & Schoenheimer (1989), Vellutino (1987), Wiig & Abele (1981) and Vodel (1977) are all agreed that the problem in these people of speech disorders is that they face problems in using language structures. Pearl & Bryant (1981) adds that as a result of the above mentioned reasons of the special needs specialists, "these people usually allow the other party whom they speak with to dominate conversation.…”
Section: Language Aspects Overcome By Dafmentioning
confidence: 99%